Co-producing healthcare in a volume vs. value-based healthcare system: perspective of a parent of a patient and a health professions’ educator - Rosemary Caron (The Beryl Institute, 2019)
The Institute for Healthcare Improvement’s Triple Aim framework represents an approach to optimizing a health system’s performance by focusing on improving the patient experience of care, improving the health of populations, and reducing healthcare costs. As the US healthcare system undergoes substantial reformation and a shift from fee-for-service payment to value-based models, an approach that emphasizes the co-production of healthcare, our healthcare system must work in concert with the Triple Aim to improve the health experience for patients across multiple environments. Co-production in healthcare means that patients contribute to the provision of health services as partners of professional providers. To highlight how the current healthcare model failed a patient by delaying diagnosis and subsequent care, thus causing undue suffering, the personal experience of one of the author’s children is reported as a narrative. The purpose of communicating this patient experience is to: 1) remind healthcare providers about the importance of not only listening, but hearing the patient and their parent’s concerns; 2) readily admit when a patient’s clinical presentation falls outside of their expertise; and 3) co-produce healthcare by working with the patient and their family. This patient experience serves to reinforce the commitment to co-produce health with patients and their families in a manner that emphasizes the value of care. Experience Framework This article is associated with the Innovation & Technology lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Innovation%20%26%20Technology%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens